Intelligent material for realizing self-healing by utilizing monomer liquid and catalyst and application
By using monomer liquids and catalysts in concrete, efficient crack repair and strength improvement are achieved, and the problems of low repair efficiency and reduced strength in the prior art are solved.
Patent Information
- Application Number
- CN202510035304.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-25
AI Technical Summary
The existing concrete self-repair technology has low restoration efficiency and the material strength will be reduced after restoration.
Using monomer liquids and catalysts, by adding monomer liquid compounds and composite catalysts to the concrete, the water-absorbing resin is used to absorb oxygen and moisture, and a rapid polymerization reaction occurs under natural heating or hydration exothermic conditions to form polymers of high strength and density, filling cracks and forming a support network.
Efficient crack repair and concrete strength improvement are achieved, avoiding further crack expansion and material strength reduction.
Smart Images

Figure CN119874284A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete self-repairing materials, and in particular to an intelligent material and application thereof which realizes self-healing by using monomer liquid and catalyst. Background Art
[0002] Concrete is an artificial stone made by mixing cementitious materials, aggregates, water, admixtures and additives in a certain proportion. It has high compressive strength and good durability. It is the largest and most widely used building material in the world today. However, its brittle nature makes it have poor crack resistance and it is easy to crack under the action of ambient temperature or load. If these cracks are not repaired in time, the cracks in the concrete will easily deepen, and moisture and other harmful substances in the air will enter the interior of the concrete and cause erosion, reducing the mechanical properties of the concrete material. In severe cases, it will cause wall collapse, posing a threat to personal safety and the risk of economic loss.
[0003] Currently, there are two main ways to repair concrete materials: manual repair and automatic repair. The traditional manual repair method has a better repair effect, but this method can only repair cracks visible to the naked eye. It is difficult to detect and repair internal damage to the concrete in time. At the same time, manual repair is helpless for cracks in some special structures and cracks in dangerous environments, and has certain limitations. In order to make up for the limitations of manual repair technology, people have developed automatic concrete repair technology on this basis.
[0004] Self-repairing technologies generally include pre-embedded shape memory alloy methods, bionic self-healing technologies, and microbial induced calcium carbonate precipitation technologies. Among them, the pre-embedded shape memory alloy method mainly uses pre-embedded memory alloy metal in concrete. When cracks occur in concrete, the memory alloy is deformed by powering on and heating to achieve self-repair of the concrete. This method has a good repair effect, but it consumes a lot of energy and has high costs, which has certain limitations in market promotion; the bionic self-healing technology mainly embeds the repair material in microspheres. When cracks occur in concrete, the microspheres break, and the repair material flows out to fill the cracks, thereby achieving the self-repair effect of the concrete. Although this method can achieve self-repair of concrete to a certain extent, the repair material has poor compatibility with concrete and is easily lost under wind or rain erosion, resulting in poor repair effect.
[0005] The existing self-healing technology has low repair efficiency, and the strength of the material will be reduced after self-healing. However, ionic interaction has the characteristics of highly adjustable bond energy, easy aggregation and highly reversible aggregation, which makes ionic interaction have great prospects in constructing high-performance self-healing materials.
[0006] Therefore, efficient and strong self-healing can be achieved using monomer liquid and catalyst. Summary of the invention
[0007] Purpose of the invention: In view of the defects of the prior art, the purpose of the present invention is to provide an intelligent material and application that uses monomer liquid and catalyst to achieve self-healing, which has high repair efficiency and can improve material strength after repair.
[0008] Technical solution:
[0009] A smart material that realizes self-healing by using a monomer liquid and a catalyst, comprising a monomer liquid compound, a water-absorbing resin, silicon dioxide, calcium oxide, a composite catalyst and cement;
[0010] The composite catalyst is prepared by compounding an azo catalyst and an oxidation catalyst;
[0011] The monomer liquid compound has a structure as shown in the following formula A:
[0012]
[0013] The present invention adds a monomer liquid compound and a composite catalyst to the repair material, and when cracks occur in the concrete, the water-absorbing resin can absorb oxygen and moisture in the air, and a rapid polymerization reaction occurs after natural heating or hydration heat release, thereby forming a polymer form with high strength and density. Not only can the repair material be absorbed and quickly filled into the concrete cracks to achieve a self-repairing effect of the cracks, but a high-strength support network can also be formed to prevent further expansion of the cracks and reduction in the strength of the concrete material.
[0014] Furthermore, the water-absorbing resin is selected from one of sodium acrylate water-absorbing resins, polyacrylate water-absorbing resins or starch acrylate water-absorbing resins.
[0015] Furthermore, the azo catalyst is selected from one of azobisisobutyronitrile, azobisisovaleronitrile or azobisisoheptylnitrile; and the oxidation catalyst is selected from one of benzoyl peroxide, dibenzoyl peroxide or tert-butyl benzoyl peroxide.
[0016] Furthermore, the mass ratio of the azo catalyst to the oxidation catalyst in the composite catalyst is (5-8): (1.5-2).
[0017] The present invention uses a composite catalyst prepared by compounding an azo catalyst and an oxidation catalyst. On the one hand, the polymerization conditions of the monomer liquid can be adjusted so that the polymerization reaction can occur under the conditions of calcium oxide hydration exothermic or natural temperature rise, thereby achieving an intelligent effect of self-healing when cracks occur in concrete; on the other hand, the composite catalyst can significantly improve the polymerization efficiency, so that the polymer can be quickly filled in the cracks of the concrete, thereby preventing the cracks from further expanding and achieving a rapid repair effect of the cracks.
[0018] Furthermore, the monomer liquid compound is prepared by the following steps: adding 5-norbornene-2,3-dimethanol, a catalyst and an organic solvent into a reactor, adding diphenyldichlorosilane dropwise after stirring evenly, stirring and reacting for 16-24 hours after the addition is completed, extracting, filtering and drying to obtain the monomer liquid compound.
[0019] The present invention uses a monomer liquid compound with a multi-ring stable structure as a polymerizable monomer. On the one hand, the benzene ring structure in the monomer liquid compound can not only improve its stability after polymerization, but also improve its steric hindrance, reduce the probability of polymerization in a low-energy environment, and then control it to initiate polymerization after cracks appear in the concrete, thereby achieving a self-repairing effect of the concrete; on the other hand, the silicon-oxygen structure in the monomer liquid compound can cross-link with each other after polymerization to form a high-strength and high-density network structure, thereby linking the concrete with other repair materials, and further improving the strength of the concrete after repair.
[0020] Furthermore, the catalyst is selected from one of triethylamine and triphenylphosphine; and the organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and tetrahydrofuran.
[0021] Furthermore, the mass ratio of 5-norbornene-2,3-dimethanol to diphenyldichlorosilane is 3-4:5.
[0022] Furthermore, the smart material that uses monomer liquid and catalyst to achieve self-healing is prepared by the following steps: in a reactor, monomer liquid compound, water-absorbing resin, silicon dioxide, calcium oxide, composite catalyst and cement are added in proportion, and the smart material that uses monomer liquid and catalyst to achieve self-healing is obtained after high-speed stirring.
[0023] Furthermore, based on the total mass fraction being 100%, the mass percentage of each component is:
[0024]
[0025] Any of the above-mentioned smart materials that use monomer liquid and catalyst to achieve self-healing are applied in the field of concrete.
[0026] Beneficial effects:
[0027] (1) The smart material provided by the present invention realizes self-healing by using monomer liquid and catalyst. By adding monomer liquid compounds and composite catalysts that can be polymerized under specific conditions, and compounding materials such as water-absorbent resin, silicon dioxide, calcium oxide and cement, it can quickly polymerize when cracks appear in concrete to achieve the self-repair effect of concrete cracks, and after polymerization, the strength of concrete can be further improved. It can be widely used in the field of concrete self-repairing material technology.
[0028] (2) The present invention provides an intelligent material that uses a monomer liquid and a catalyst to achieve self-healing. By adding a monomer liquid compound and a composite catalyst to the repair material, when cracks occur in the concrete, the water-absorbing resin can absorb oxygen and moisture in the air, and a rapid polymerization reaction occurs after natural heating or hydration heat release, thereby forming a polymer form with high strength and density. The polymer form can not only absorb the repair material and quickly fill it into the concrete cracks to achieve the self-repairing effect of the cracks, but also form a high-strength support network to prevent further expansion of the cracks and reduction in the strength of the concrete material.
[0029] (3) The present invention provides a smart material that realizes self-healing by using a monomer liquid and a catalyst. By using a monomer liquid compound with a multi-ring stable structure as a polymerizable monomer, on the one hand, the benzene ring structure in the monomer liquid compound can not only improve its stability after polymerization, but also improve its steric hindrance, reduce the probability of polymerization in a low-energy environment, and then control it to initiate polymerization after cracks appear in the concrete, thereby achieving the self-repairing effect of the concrete; on the other hand, the silicon-oxygen structure in the monomer liquid compound can cross-link with each other after polymerization to form a high-strength and high-density network structure, thereby linking the concrete with other repair materials, and further improving the strength of the concrete after repair.
[0030] (4) The present invention provides an intelligent material that realizes self-healing by using a monomer liquid and a catalyst. The material is prepared by combining an azo catalyst and an oxidizing catalyst as a composite catalyst. On the one hand, the polymerization conditions of the monomer liquid can be adjusted so that the polymerization reaction can occur under the conditions of calcium oxide hydration exothermic or natural temperature rise, thereby achieving an intelligent effect of self-healing when cracks occur in concrete. On the other hand, the composite catalyst can significantly improve the polymerization efficiency, so that the polymer can quickly fill the cracks in the concrete, avoiding further expansion of the cracks and achieving a rapid repair effect of the cracks. DETAILED DESCRIPTION
[0031] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0032] The cement is P.O52.5 type silicate cement; the commercially available concrete self-repairing material is PENG ENI CHUAN 803 waterproof additive purchased from Guangdong Zhongyouli Technology Co., Ltd.; the sodium acrylate water-absorbing resin is DMSZ-8832 purchased from Xinxiang Dongmao Environmental Protection Materials Co., Ltd.; the polyacrylate water-absorbing resin is a polymer water-absorbing resin purchased from Renqiu Hengyu Chemical Co., Ltd.; the remaining reagents and equipment are conventional reagents and equipment in this technical field.
[0033] Preparation of Monomer Liquid Compound-1
[0034] The monomer liquid compound-1 was prepared by the following steps:
[0035] In a reactor, 3 g of 5-norbornene-2,3-dimethanol, 0.1 g of triethylamine and 100 mL of dimethylformamide were added, and after stirring evenly, 5 g of diphenyldichlorosilane was added dropwise. After the addition was completed, the mixture was stirred and reacted for 24 hours. After extraction, suction filtration and drying, the monomer liquid compound-1 was obtained;
[0036] Mass spectrum data of monomer liquid compound-1: The product was analyzed by LC-MS, and the m / z of the product was 334.14 (100.0%), 335.16 (28.5%), 336.15 (7.2%), and 337.15 (1.1%).
[0037] Preparation of Monomer Liquid Compound-2
[0038] The preparation is basically the same as the monomer liquid compound-1, except that diphenyldichlorosilane is replaced by an equal amount of dimethyldichlorosilane.
[0039] Preparation of Monomer Liquid Compound-3
[0040] The preparation method is basically the same as that of the monomer liquid compound-1, except that diphenyldichlorosilane is replaced by an equal amount of 1,6-dichlorohexane.
[0041] Example 1
[0042] The self-healing smart material using monomer liquid and catalyst was prepared by the following steps:
[0043] A composite catalyst is prepared by mixing azobisisobutyronitrile and benzoyl peroxide in a mass ratio of 3:1;
[0044] In a reactor, a monomer liquid compound, a sodium acrylate water-absorbing resin, silicon dioxide, calcium oxide, a composite catalyst and cement are added in proportion, and the mixture is stirred at high speed to obtain the smart material that realizes self-healing by using the monomer liquid and the catalyst;
[0045] Taking the total mass fraction as 100%, the mass percentage of each component is:
[0046]
[0047] Example 2
[0048] The method is basically the same as Example 1, except that the composite catalyst is changed to azobisisovaleronitrile and tert-butyl benzoyl peroxide in a mass ratio of 5:1.5;
[0049] Taking the total mass fraction as 100%, the components and their mass percentages are as follows:
[0050]
[0051] Example 3
[0052] Basically the same as Example 1, except that, based on the total mass fraction being 100%, the components and their mass percentages are:
[0053]
[0054] Comparative Example 1
[0055] Commercially available concrete self-healing materials.
[0056] Comparative Example 2
[0057] The process is basically the same as Example 1, except that the monomer liquid compound-1 is replaced by an equal amount of monomer liquid compound-2.
[0058] Comparative Example 3
[0059] The process is basically the same as Example 1, except that the monomer liquid compound-1 is replaced by an equal amount of monomer liquid compound-3.
[0060] Comparative Example 4
[0061] The method is basically the same as Example 1, except that the composite catalyst is replaced by an equal amount of azobisisobutyronitrile.
[0062] Performance Testing
[0063] By weight, 50 parts of the products of Examples 1-3 and Comparative Examples 1-4 were respectively mixed with 350 parts of cement, 50 parts of fly ash, 500 parts of sand, 1000 parts of gravel and 150 parts of water to prepare concrete of the same specifications, and then cured under the same conditions for 28 days.
[0064] Mechanical strength test: According to GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Concrete", the 28d compressive strength of the above-prepared concrete was tested respectively.
[0065] Self-repairing ability test: The benchmark concrete test block prepared above was subjected to a splitting tensile test to make the benchmark concrete test block have a crack width of 0.2-0.4 mm, and the initial crack width was recorded, and the crack widths at 7d and 28d of curing were recorded respectively.
[0066] Mechanical property recovery ability test: According to GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Concrete", the compressive strength of the concrete cured for 28 days after the splitting tensile test was tested.
[0067] The test results are shown in the following table:
[0068]
[0069] According to the comparison of the test results of Examples 1-3 with those of Comparative Example 1, the smart material provided by the present invention that realizes self-healing by using monomer liquid and catalyst has a better repair efficiency than the self-repairing material in the prior art, and can improve the mechanical strength of the repaired concrete.
[0070] According to the comparison of the test results of Examples 1-3 and Comparative Examples 2-3, the smart material provided by the present invention that realizes self-healing by using monomer liquid and catalyst can effectively realize the self-repairing effect and improve the mechanical strength of the repaired concrete by using the monomer liquid compound as a polymerizable monomer.
[0071] According to the comparison of the test results of Examples 1-3 and Comparative Example 4, the smart material for self-healing using monomer liquid and catalyst provided by the present invention uses a composite catalyst prepared by combining an azo catalyst and an oxidizing catalyst, which can significantly improve the polymerization efficiency of the monomer liquid, thereby achieving a rapid repair effect of cracks.
[0072] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A smart material that achieves self-healing using a monomer liquid and a catalyst, characterized in that: Containing a monomer liquid compound, a water-absorbing resin, silicon dioxide, calcium oxide, a composite catalyst and cement; The composite catalyst is prepared by compounding an azo catalyst and an oxidation catalyst; The monomer liquid compound has a structure as shown in the following formula A:
2. The smart material for achieving self-healing by using monomer liquid and catalyst according to claim 1, characterized in that: The water-absorbing resin is selected from one of sodium acrylate water-absorbing resins, polyacrylate water-absorbing resins or starch acrylate water-absorbing resins.
3. The smart material for achieving self-healing by using monomer liquid and catalyst according to claim 1, characterized in that: The azo catalyst is selected from one of azobisisobutyronitrile, azobisisovaleronitrile or azobisisoheptanenitrile; the oxidation catalyst is selected from one of benzoyl peroxide, dibenzoyl peroxide or tert-butyl benzoyl peroxide.
4. The smart material for achieving self-healing by using monomer liquid and catalyst according to claim 3, characterized in that: The mass ratio of the azo catalyst to the oxidation catalyst in the composite catalyst is (5-8)::(1.5-2).
5. The smart material for achieving self-healing by using monomer liquid and catalyst according to claim 1, characterized in that: The monomer liquid compound is prepared by the following steps: adding 5-norbornene-2,3-dimethanol, a catalyst and an organic solvent into a reactor, adding diphenyldichlorosilane dropwise after stirring evenly, stirring and reacting for 16-24 hours after the addition is completed, extracting, filtering and drying to obtain the monomer liquid compound.
6. The smart material for achieving self-healing by using monomer liquid and catalyst according to claim 5, characterized in that: The catalyst is selected from one of triethylamine and triphenylphosphine; and the organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and tetrahydrofuran.
7. The smart material for achieving self-healing by using monomer liquid and catalyst according to claim 5, characterized in that: The mass ratio of the 5-norbornene-2,3-dimethanol to diphenyldichlorosilane is 3-4:
5.
8. The smart material for achieving self-healing by using monomer liquid and catalyst according to claim 1, characterized in that: The smart material that uses monomer liquid and catalyst to achieve self-healing is prepared by the following steps: in a reactor, monomer liquid compound, water-absorbing resin, silicon dioxide, calcium oxide, composite catalyst and cement are added in proportion, and the smart material that uses monomer liquid and catalyst to achieve self-healing is obtained after high-speed stirring.
9. The smart material for achieving self-healing by using monomer liquid and catalyst according to claim 8, characterized in that: Taking the total mass fraction as 100%, the mass percentage of each component is: The balance is cement.
10. Application of the smart material realizing self-healing by using monomer liquid and catalyst as claimed in any one of claims 1 to 9 in the field of concrete.